Penguatan Nilai Kewarganegaraan dan Sikap Toleransi melalui Aktivitas Literasi di Masyarakat Multikultural : Pengabdian - Yolandari, Joesa; Zulyan, Zulyan; Mitha, Anisia Nur; Yudha, Romadhona Kusuma; Rizki, Rizki (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Strengthening civic values ​​and mutual respect is crucial in today's multicultural society in Indonesia. Through literacy activities, this community service aims to raise awareness of differences and strengthen national identity. It was implemented through participatory methods, including forming reading groups and discussing tolerance, Pancasila, and inspiring stories from various cultures. The target group for this activity was the community in Air Manna 1 Village, Bengkulu City, which has diverse ethnic and religious backgrounds. The results of this activity indicate that residents' understanding of the values ​​of diversity and the spirit of tolerance has increased. Literacy activities have proven to be an effective means of strengthening inclusive civic character.